2009
DOI: 10.1016/j.gie.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Confocal laser endomicroscopy in Barrett's esophagus and endoscopically inapparent Barrett's neoplasia: a prospective, randomized, double-blind, controlled, crossover trial

Abstract: Background-The detection of high grade dysplasia and cancer in Barrett's esophagus (BE) can be challenging. Confocal laser endomicroscopy (CLE) allows in vivo visualization of mucosal histology during endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(125 citation statements)
references
References 28 publications
3
116
0
6
Order By: Relevance
“…This technique also showed good performance for the diagnosis of BE associated neoplasia, with a sensitivity and specificity of 92.9% and 98.4% respectively (49). Moreover, additional studies have shown that the use of eCLE with targeted biopsies has a higher diagnostic yield for BE associated neoplasia compared to standard biopsy protocol, with reduction in the number of biopsies needed (50,51). Real-time microscopic visualization of the mucosa is also achieved with the use of endocytoscopy, however its use has been limited in the management of BE patients due to poor image quality (48).…”
Section: Diagnosis Of Bementioning
confidence: 89%
“…This technique also showed good performance for the diagnosis of BE associated neoplasia, with a sensitivity and specificity of 92.9% and 98.4% respectively (49). Moreover, additional studies have shown that the use of eCLE with targeted biopsies has a higher diagnostic yield for BE associated neoplasia compared to standard biopsy protocol, with reduction in the number of biopsies needed (50,51). Real-time microscopic visualization of the mucosa is also achieved with the use of endocytoscopy, however its use has been limited in the management of BE patients due to poor image quality (48).…”
Section: Diagnosis Of Bementioning
confidence: 89%
“…A follow-up cross over study compared routine quadrant biopsies with biopsies targeted by eCLE. The per biopsy diagnostic yield was almost doubled by CLE, and two thirds of patients did not need any biopsy based on normal appearance of their Barrett's segment with CLE [21].…”
Section: Endomicroscopy In the Esophagusmentioning
confidence: 99%
“…Within larger lesions, the most suspicious part can be identified and targeted for physical tissue sampling. In studies, such a concept of microscopically targeted, "smart" biopsies has resulted in fewer biopsies, but higher yield to detect neoplasia in the upper [21] and lower GI tract [22].…”
Section: In Vivo Imaging and Staining Protocolsmentioning
confidence: 99%
“…A better rationale for reimbursing CLE at a higher level may be that it appears to safely reduce the number of biopsies needed for surveillance. The data of Dunbar et al 27 suggest that its added value for Barrett esophagus patients compared to conventional endoscopy could be as high as the charges for 10 endoscopic biopsies. The data of Kiesslich et al 21 suggest that 70 CLE images can substitute for about 30 endoscopic biopsies for cancer surveillance in ulcerative colitis.…”
Section: Limitations Of Confocalmentioning
confidence: 99%
“…Half as many eCLE-targeted biopsies (10 fewer per patient) detected the same number of high-grade lesions as standard surveillance biopsies. 27 The theme that emerges from this and the colonic findings is that CLE has value in decreasing the number of biopsies required. High interobserver agreement has been achieved for diagnosis of dysplasia by CLE in Barrett esophagus, with a k value of 0.83.…”
mentioning
confidence: 92%